REPRESENTASI ISU SOSIAL MASYARAKAT PADA NOVEL KITA PERGI HARI INI KARYA ZIGGY ZESYAZEOVIENNAZABRIZKIE (PENDEKATAN SOSIOLOGI SASTRA) - Angeline, Brigita Agnes; Seli, Sesilia; Sanulita, Henny (Universitas Tanjungpura, 2025)
This research aims to uncover the representation of social issues in the novel Kita Pergi Hari Ini by Ziggy Zesyazeoviennazabrizkie through a literary sociology approach. The method used is descriptive with the form of qualitative research and data collection through documentary techniques. The data analyzed included words, phrases, sentences, and dialogues in the novel Kita Pergi Hari Ini by Ziggy Zesyazeoviennazabrizkie. The results of this study show that first, this novel represents social issues, especially poverty seen from five aspects, namely, labor slavery, economic difficulties, areas of commotion, out-of-control child births, and population density. Second, this novel represents the issue of social inequality seen from four aspects, namely, the environment, limited employment, infrastructure, and resource control. Third, this research produced a text-based teaching module from the novel Kita Pergi Hari Ini by Ziggy Zesyazeoviennazabrizkie as a learning material in high school grade XII. This research is expected to increase understanding of the rule of literature in representing social issues in society.